Posterior reversible encephalopathy syndrome complicating diabetic ketoacidosis; an important treatable complication. Issue 2 (14th January 2016) - Jones, Rachel; Redler, Kasey; Witherick, Jonathan; Fuller, Geraint; Mahajan, Tripti; Wakerley, Benjamin R.
Abstract : Development of acute neurological symptoms secondary to cerebral oedema is well described in diabetic ketoacidosis (DKA) and often has a poor prognosis. We present the clinical and radiological data of a 17‐yr‐old girl who developed cortical blindness, progressive encephalopathy, and seizures caused by posterior reversible encephalopathy syndrome (PRES) that developed after her DKA had resolved. Vasogenic oedema in PRES resolves if the underlying trigger is identified and eliminated. In this case, hypertension was identified as the likely precipitating factor and following treatment her vision and neurological symptoms rapidly improved. We suggest how recent DKA may have contributed to the development of PRES in this patient.